“REPRESSED” TERMS IN TRANSLATION DICTIONARIES OF UKRAINIAN TERMINOLOGICAL SCHOOLS - Oksana H. Lytvyn (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
This article elucidates a problem of restoring ideologically removed terminological units to modern technical terminology. “Russian-Ukrainian dictionary of scientific terminology. Mathematics. Physics. Earth and Space Sciences”, published in Kyiv in 1998, “Defining Russian-Ukrainian-English Dictionary of Energy” edited by A. Rudnik, published in Kharkiv in 1999 and “Russian-Ukrainian Dictionary of Engineering Technologies” from the terminographic series Word World, published in Lviv in 2013 were analyzed. “Repressed” terms have been found in all analyzed lexicographic works, prepared and published by various Ukrainian schools. Having analyzed the term material of these terminological works, it has been noted that all the authors of mentioned dictionaries reasonably continue to revive the authentic Ukrainian terms. The purpose of the article is to identify tendencies of standardization of Ukrainian technical terminology, common for domestic terminological schools, on the basis of the analysis of “repressed” terms recorded in modern lexicographical works. In the dictionary article they clearly put terms on the first place, that are recommended by the permanent scientific terminological seminar of the Technical Committee for Standardization of Scientific and Technical Terminology of Derzhspozhyvstandart and the Ministry of Education and Science of Ukraine, as well as the requirements of the State Standard. It was discovered that lexicographers of Lviv Polytechnic consistently continue the traditions of Ukrainian terminologists of the 1920s, who were employees of the Institute of Scientific Language of the Ukrainian Academy of Sciences, and use methods of describing terminological material typical for the “golden decade” Ukrainian terminology. Descriptive-analytical and comparative methods are applied in the study, according to which the observation of the analyzed lexicographic material is generalized, in particular, the terms that were removed from the Ukrainian technical terminology in the 30s of the twentieth century by terminological bulletins are described. The structural method contributes to the description of word-forming affixes of the studied terms. Analytical and synthetic elaboration of terminographic sources is used to shed light on the historiography of this issue. Based on the analytical-synthetic elaboration of lexicographic works of three domestic terminological schools, the article reveals the following common tendencies of standardization of Ukrainian technical terminology: return to the terminology of unfairly forgotten or forcibly removed nominations; creation of new terms according to Ukrainian word-forming models, restoration of etymological writing and sounding of technical terms; arranging scientific and technical dictionaries by teams of authors – specialists in various technical fields and terminographs; the common position of domestic terminological schools is to focus on the native language soil, taking into account the achievements of previous generations